Variability in the syntax of idioms - Hladnik, Marko (ELOPE (Ljubljana), 2017)
Given that the meaning of idioms is not predictable from the literal meaning of their parts, we can broadly define idioms as expressions with a non-compositional interpretation. Since language is a compositional system, this characteristic of idioms might suggest that they are atomic building blocks of language with no internal syntax. However, that turns out not to be the case. This paper explores the syntax of English verbal idioms and their degree of compositionality. Idioms do have an internal syntactic structure that is actually variable to an extent and, despite being superficially similar, different idioms exhibit different syntactic properties. The topics discussed include the variability of determiners in idioms, the subcategorisation of idioms based on their relative compositionality into two groups that behave differently with respect to their syntactic flexibility, and the identification of grammatical categories that are obligatory components of certain idioms but not others.
Keywords: določilniki; idiomi; kompozicionalnost; pasivizacija; skladnja; syntax